2021
DOI: 10.3389/fpsyt.2020.561790
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Family-Based Intervention Program for Children of Mentally Ill Parents: Study Protocol for a Randomized Controlled Multicenter Trial

Abstract: Background: Children of mentally ill parents have a three to seven times higher risk of developing mental disorders compared to the general population. For this high-risk group, specialized prevention and intervention programs have already been developed. However, there has been insufficient sytematic evaluation to date. Moreover, effectiveness and the cost-effectiveness data of the respective programs until today is very scarce and at the same time constitutes the pre-condition for the program's implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
(31 reference statements)
1
18
0
1
Order By: Relevance
“…Our results are close to those reported by Ito et al’s [ 17 ] pilot study, whereby work-focused cognitive behavioral group therapy (8 sessions) for Japanese workers on sick leave due to depression resulted in improvements in anxiety and depressive symptoms, as well as in social functioning from pre to post intervention. Our results are also close to those of Winter et al [ 46 ], who conducted a pilot study with 20 German workers with a major depression who received cognitive-behavioral therapy, with an integrated, standardized RTW module (W-CBT). They also found that work ability significantly improved and depressive symptoms were significantly reduced in their pre-post comparison.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are close to those reported by Ito et al’s [ 17 ] pilot study, whereby work-focused cognitive behavioral group therapy (8 sessions) for Japanese workers on sick leave due to depression resulted in improvements in anxiety and depressive symptoms, as well as in social functioning from pre to post intervention. Our results are also close to those of Winter et al [ 46 ], who conducted a pilot study with 20 German workers with a major depression who received cognitive-behavioral therapy, with an integrated, standardized RTW module (W-CBT). They also found that work ability significantly improved and depressive symptoms were significantly reduced in their pre-post comparison.…”
Section: Discussionsupporting
confidence: 90%
“…Given that depressive and anxiety symptoms can negatively impact one’s RTW, it is important to consider both clinical and work outcomes when evaluating RTW and work sustainability. Recent developments for preventing sustained or recurrent depressive symptoms after RTW can be found in the literature, mostly favoring interventions using cognitive behavioral concepts and strategies, either in group or individual formats [ 16 , 17 , 46 ]. According to Arends et al’s [ 24 ] trajectory analyses following RTW after a CMD-related sick leave, workers continue to experience work functioning and clinical challenges over time, even at one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized data from the baseline assessment of a randomized controlled trial ("Implementation and evaluation of a family-based intervention program for children of mentally ill parents: a randomized controlled multicenter trial") funded by the German Federal Ministry of Education and Research (BMBF). Details of the study have been reported elsewhere [45]. Data were gathered between 2014 and 2017.…”
Section: Methodsmentioning
confidence: 99%
“…For the present analyses, a cross-sectional one-group design was used. Data from the baseline assessment of a multicenter randomized controlled trial were used (“Implementation and evaluation of a family-based intervention program for children of mentally ill parents: a randomized controlled multicenter trial”; for study protocol, see Wiegand-Grefe et al, 2021 ). The trial was conducted at seven clinical centers located in Germany and Switzerland.…”
Section: Methodsmentioning
confidence: 99%